Judicial cooperation in criminal matters in the Special Administrative Regions of Hong Kong and Macau. Through the lens of “one country, two systems” and the surrender of fugitives to Mainland China - Miguel Manero de Lemos; Teresa Lancry Robalo (Revista Brasileira de Direito Processual Penal, 2019)
This Article proceeds in three parts. Part I (The constitutional systems of the Special Administrative Regions of Hong Kong and Macau) introduces the readers to the historical background of Hong Kong and Macau and the “one country, two systems” constitutional orders in force in the Hong Kong and the Macau Special Administrative Regions of the People’s Republic of China. It also informs on the most relevant constitutional developments occurring in the first two decades of existence of these two special regions. Part II (Judicial cooperation in criminal matters in the Special Administrative Regions) explains how such constitutional orders influence the extant legal framework on judicial cooperation in criminal matters, which applies to external cooperation with other states or territories, but not to cooperation between the different jurisdictions within China, for which there are no positive rules currently in force. This part surveys the rules in force in Hong Kong and Macau concerning the surrender of fugitives to other countries. Part III (The surrender of fugitives to Mainland China) focuses particularly on the issue of arrest and return of Chinese citizens from Hong Kong and Macau to Mainland China. It provides an overview of the cases that came to public attention and the legal conundrums created by the absence of “two systems” specific rules on surrender of fugitives within “one country”.